Nutrition-Based Support for Osteoporosis in Postmenopausal Women: A Review of Recent Evidence - Alabadi B; Civera M; Moreno-Errasquin B; Cruz-Jentoft AJ (Dove Medical Press, 2024)
Blanca Alabadi,1,2,* Miguel Civera,1,3,* Beatriz Moreno-Errasquin,4 Alfonso J Cruz-Jentoft4 1Service of Endocrinology and Nutrition, Hospital Clinico Universitario of Valencia, Valencia, 46010, Spain; 2INCLIVA Biomedical Research Institute, Valencia, 46010, Spain; 3Department of Medicine, University of Valencia, Valencia, 46010, Spain; 4Servicio de Geriatría, Hospital Universitario Ramón y Cajal (IRYCIS), Madrid, 28034, Spain*These authors contributed equally to this workCorrespondence: Blanca Alabadi, Av. Blasco Ibañez, 17, Valencia, 46010, Spain, Email balabadi@incliva.esAbstract: Postmenopausal osteoporosis stands as the predominant bone disorder in the developed world, posing a significant public health challenge. Nutritional factors play a crucial role in bone health and may contribute to its prevention or treatment. Calcium and vitamin D, extensively studied with robust scientific evidence, are integral components of the non-pharmacological treatment for this disorder. Nevertheless, other less-explored nutritional elements appear to influence bone metabolism. This review provides a comprehensive summary of the latest evidence concerning the relationship between various nutrients, such as phosphorus, magnesium, vitamins, phytate, and phytoestrogens; specific foods like dairy or soy, and dietary patterns such as the Mediterranean diet with bone health and osteoporosis.Keywords: postmenopausal osteoporosis, nutrition, micronutrients, bone health, dietary interventions, food components